Livestock nutrition in the dry tropics of Africa - Mosi, A.K.; Tessema, S.; Temple, R.S. (International Feedstuffs Institute, 1977)
Assesses the nutritive value of prevailing herbage in the dry tropics of Africa, outlining herbage palatability, intake, digestibility, chemical composition as well as mineral & energy potentials; discusses the effect of the parameters on the performance of grazing animals.